TOTAL BAKTERI ASAM LAKTAT DAN COLIFORM USUS ITIK CIHATEUP YANG DIBERI PAKAN MENGANDUNG KOMBINASI TEPUNG KULIT MANGGIS DAN KUNYIT (Total Lactic Acid Bacteria and Coliform of Cihateup Ducks Intestine that Given Feed Containing the Combination of Mangosteen Peel and Turmeric Flour) - Andri Kusmayadi; Novia Rahayu (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2020)
The number of beneficial microbial populations (lactic acid bacteria/LAB) and pathogens (coliform) in the digestive tract of ducks is one indicator of duck health status. Healthy ducks have a beneficial microbial population more than pathogenic bacteria. The addition of herbal ingredients such as mangosteen peel and turmeric flour is thought to improve the health of ducks by increasing the LAB population. The purpose of this study was to examine the effect of the combination of mangosteen peel flour and turmeric flour on the total lactic acid bacteria and coliform of small intestine and caecum of Cihateup duck. The study was conducted experimentally using 60 male Cihateup ducks grouped into 5 feed treatments which contains a combination of mangosteen peel and turmeric flour at different levels as follows: 0.5% (R1); 1.0% (R2); 1.5% (R3); 2.0% (R4); and 2.5% (R5), respectively. The variables studied were total lactic acid and coliform bacteria in the small intestine and caecum of Cihateup ducks. The results showed that the treatments of feed significantly (P<0.05) affected the total lactic acid bacteria (except caecum) and coliform bacteria. The population of lactic acid bacteria tended to increase along with the increasing dose of combination treatment of mangosteen peel and turmeric flour. In contrast, the total population of coliform bacteria in the small intestine and caecum of ducks showed a tendency to decrease with increasing treatment doses. The use of a combination of mangosteen peel and turmeric flour at higher levels (2.0 – 2.5%) can increase the total LAB and decrease coliform bacteria in the small intestine and cecum of Cihateup duck.